2020
DOI: 10.3390/microorganisms8071071
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Production by Enterotoxigenic Strains of Bacillus cereus in Different Materials and under Different Environmental Conditions

Abstract: Foodborne illnesses, such as infections or food poisoning, can be caused by bacterial biofilms present in food matrices or machinery. The production of biofilms by several strains of Bacillus cereus on different materials under different culture conditions was determined, as well as the relationship of biofilms with motility, in addition to the enterotoxigenic profile and candidate genes that participate in the production of biofilms. Biofilm production of B. cereus strains was determined on five materials: gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…However, in this study, the production of biofilms was low, and as the frequency of the sipW and tasA genes. In a previous study, we found a differential distribution of the sipW and tasA genes according to the origin of the B. cereus strains, finding a high frequency in strains from eggs compared to strains from other foods ( Adame-Gómez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, in this study, the production of biofilms was low, and as the frequency of the sipW and tasA genes. In a previous study, we found a differential distribution of the sipW and tasA genes according to the origin of the B. cereus strains, finding a high frequency in strains from eggs compared to strains from other foods ( Adame-Gómez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…In brief, cells from one colony were suspended in sterile water, heated at 95 °C for 3 min, and then placed on ice. After centrifugation, the supernatant was used as template for the molecular identification and toxin profile ( Adame-Gómez et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…B. cereus BC133 strain was used as a positive control for nhe amplification. This strain was previously isolated and characterized in the laboratory from infant formula powdered [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The production of biofilms was carried out with 1 mL of BHI broth in glass tubes (CLS99447161, Merck, Darmstadt, Germany) containing 50 μL of a 24 h culture. They were incubated for 48 h, and washed three times with phosphate-buffered saline or PBS 1X (NaCl 137 mM, KCl 2.7 mM, Na 2 HPO 4 10 mM, KH 2 PO 4 1.8 mM, pH 7.2); 1 mL of safranin was added and homogenized for 15 min, three washes with PBS solution were performed, and it was determined from the visual observation of a ring stained by the dye [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…In brief, cells from one colony were suspended in sterile water, heated at 95ºC for 3 min, and then placed on ice. After centrifugation, the supernatant was used as template for the molecular identification and toxin profile (Adame-Gómez et al, 2020). The differentiation of B. cereus group was targeted on gyrB gene, and the toxin gene profiles from nheABC, hblABD, ces, and cytK gene.…”
Section: Molecular Identification and Toxin Gene Profiling Of B Cereu...mentioning
confidence: 99%